Digital Compliance as a Trust Framework: Constructing Tourist Confidence in Bali’s Cultural Tourism Ticket Market - I Nengah Subadra; Made Sudiarta; Ida Bagus Nyoman Krisna Prawira Yuda; I Wayan Bratayasa (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
The digitalisation of Bali’s cultural tourism ticketing systems introduces critical trust challenges by shifting transactions from interpersonal exchanges to interface mediated encounters. While adherence to digital compliance standards such as data security, privacy, and consumer protection is increasingly mandated, the ways in which these regulatory and technological cues actively construct tourist trust within culturally sensitive contexts remain underexplored. Addressing this gap, this study adopts a Grounded Theory approach to develop a contextualised understanding of how digital compliance is interpreted and psychologically experienced by tourists in Bali’s cultural tourism market. Drawing on in-depth interviews tourism stakeholders with tourists, tourism operators, and platform intermediaries, the study inductively examines how trust emerges through interactions with digitally compliant systems. Through iterative coding and constant comparison, the analysis generates a four-dimensional compliance framework encompassing data security, transactional integrity, institutional legitimacy, and platform reliability. The findings reveal trust as a processual and situational outcome, assembled through compliance cues at critical transactional moments and shaped by Bali’s socio-cultural expectations of authenticity and ethical conduct. This study contributes a grounded, empirically derived model for designing trustworthy digital ecosystems in culturally embedded tourism destinations worldwide.